Quantifying the Role of Seasonality in the Marine Carbon Cycle Feedback: An ESM2M Case Study. Issue 6 (6th June 2022) - Fassbender, Andrea J.; Schlunegger, Sarah; Rodgers, Keith B.; Dunne, John P.
Abstract: Observations and climate models indicate that changes in the seasonal amplitude of sea surface carbon dioxide partial pressure (A‐ p CO2 ) are underway and driven primarily by anthropogenic carbon (Cant ) accumulation in the ocean. This occurs because p CO2 is more responsive to seasonal changes in physics (including warming) and biology in an ocean that contains more Cant . A‐ p CO2 changes have the potential to alter annual ocean carbon uptake and contribute to the overall marine carbon cycle feedback. Using the GFDL ESM2M Large Ensemble and a novel analysis framework, we quantify the influence of Cant accumulation on p CO2 seasonal cycles and sea‐air CO2 fluxes. Specifically, we reconstruct alternative evolutions of the contemporary ocean state in which the sensitivity of p CO2 to seasonal thermal and biophysical variation is fixed at preindustrial levels, however the background, mean‐state p CO2 fully responds to anthropogenic forcing. We find near‐global A‐ p CO2 increases of >100% by 2100, under RCP8.5 forcing, with rising Cant accounting for ∼100% of thermal and ∼50% of nonthermal p CO2 component amplitude changes. The other ∼50% of nonthermal p CO2 component changes are attributed to modeled changes in ocean physics and biology caused by climate change. Cant ‐induced A‐ p CO2 changes cause an 8.1 ± 0.4% (ensemble mean ± 1σ) increase in ocean carbon uptake by 2100. This is because greater wintertime wind speeds enhance the impact of wintertime p CO2 changes, which work to increase the ocean carbon sink. Thus, the seasonal ocean carbon cycle feedback works in opposition to the larger, mean‐state feedback that reduces ocean carbon uptake by ∼60%. Plain Language Summary: Using simulations of an Earth System Model, we isolate different factors contributing to future changes in the surface ocean carbon dioxide partial pressure ( p CO2 ). We examine how the seasonal cycle of p CO2, and the associated sea‐air exchange of CO2, responds to changes in the ocean's temperature, circulation, biology, and chemistry. We find that the p CO2 seasonal cycle is significantly amplified across the global ocean (by ∼100% on average). This occurs because p CO2 is more responsive to seasonal changes in temperature as well as biological and physical (biophysical) processes in a future ocean that contains more anthropogenic carbon (Cant ). The increased temperature sensitivity is almost exclusively due to added Cant . The increased biophysical sensitivity is equally due to added Cant and changes in ocean physics and biology caused by climate change. Seasonal wind speed variation systematically enhances the impact of altered p CO2 seasonal cycles during wintertime, causing an 8% increase in the ocean carbon sink strength by the year 2100. Within the evaluated model, this indicates that the seasonal ocean carbon cycle feedback works in opposition to the larger, mean‐state ocean carbon cycle feedback, which may cause up to a ∼60% reduction in the ocean sink by the year 2100. Key Points: Ocean anthropogenic carbon (Cant ) accumulation enhances the sensitivity of ocean carbon dioxide partial pressure ( p CO2 ) to seasonal changes in ocean physics and biology Cant ‐induced changes in the p CO2 seasonal cycle under RCP8.5 forcing increase cumulative ocean carbon uptake by 8% in ESM2M The net increase in cumulative ocean carbon uptake is driven by the interaction of wintertime changes in p CO2 and strong winter winds